On the Gravitational Properties of Dark Matter - B. Al-Khasawneh; M.B. Altaie (Jordan Journal of Physics, 2025)
Analyzing ten known galactic clusters, we were able to identify a serious mass discrepancy when comparing masses calculated from the velocity dispersions of galaxies through virial method and the masses estimated through gravitational lensing. The masses obtained through virial theorem are more than twice those obtained from weak gravitational lensing observations. This might indicate that the equivalence of inertial and gravitational mass is violated in the case of dark matter. Keywords: Dark matter; Gravitational mass; Inertial mass; Virial theorem.